The Influence of Product Quality, Price and Brand Image on Purchase Decisions of Indosat Ooredoo Prepaid Cards in Makassar City - Abdullah, Abdullah; Jam’an, Andi; Indrayani3, Syarthini (Journal of Finance and Business Digital, 2024)
The objective of this research is to analyze the influence of product quality, price, and brand image on the purchasing decisions of Indosat Ooredoo prepaid cards in Makassar City. This study employs a quantitative approach. The purposive sampling technique was used to determine the sample, consisting of 65 respondents who are users of Indosat Ooredoo prepaid cards in Makassar City. Data analysis was performed using multiple linear regression, while hypothesis testing was conducted through t-statistical tests. The results of the study indicate that: (1) Product Quality has a positive and significant influence on the purchasing decisions of Indosat Ooredoo prepaid cards. (2) Price has a positive and significant influence on the purchasing decisions of Indosat Ooredoo prepaid cards. (3) Brand Image has a positive and significant influence on the purchasing decisions of Indosat Ooredoo prepaid cards.